Early histological changes of bronchopulmonary dysplasia and pulmonary hypertension may precede clinical diagnosis in preterm infants. (August 2022) - Stone, Amelia; Poulik, Janet; Koussa, Sara; Xin, Yuemin; Sharma, Amit; Sood, Beena G.
Abstract: Bronchopulmonary Dysplasia (BPD), the commonest complication of prematurity, is defined by treatment with oxygen for ≥28 days. Pulmonary hypertension (PH) often coexists with BPD and is associated with increased mortality. In 42 autopsies, histological changes of BPD and PH were demonstrated in 25 % and 65 % respectively of preterm infants <28 days of age, highlighting the need for early diagnosis and treatment. Highlights: Bronchopulmonary Dysplasia (BPD) is the commonest complication of prematurity. BPD is clinically defined by treatment with oxygen for ≥28 days. Pulmonary hypertension (PH) often coexists with BPD and increases mortality. We report histologic BPD and PH in preterm infants treated with oxygen for <28 days. Current clinical definitions do not allow for early diagnosis of BPD and PH.